Evaluation of MK filters for recovery of enteroviruses from tap water. - Ma, J F (1994)
The MK filter is an electropositively charged filter that can be used to concentrate enteroviruses from large volumes (400 to 1,000 liters) of water. This filter is less expensive than the commonly used 1MDS electropositive filter. In this study, we compared the recovery of poliovirus 1 (PV1) and that of coxsackievirus B3 (CB3) from 378 liters of tap water, using both the MK and the 1MDS filters. Viruses were eluted from the filters with 3% beef extract buffered with 0.05 M glycine (pH 9.5) and reconcentrated via organic flocculation. At high virus inputs (approximately 10(6) PFU), the overall recovery (after elution and reconcentration) of PV1 and CB3 from tap water with the MK filter was less than that achieved with the 1MDS filter (P < 0.05). The recoveries of PV1 from tap water with the MK and 1MDS filters were 73.2% +/- 26% (n = 5 trials) and 90.2% +/- 5.9% (n = 5 trials), respectively. The recoveries of CB3 from tap water with the MK and 1MDS filters were 32.8% +/- 34.5% (n = 4 trials) and 95.8% +/- 12.0% (n = 4 trials), respectively. This study indicated that the MK filter consistently provided lower recovery, with wider variability, of PV1 and CB3 from tap water than the 1MDS filter.